Pemberdayaan guru melalui kegiatan pelatihan media pembelajaran di SMK Negeri 1 Takalar - Mustari S. Lamada (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
The objectives of this study were to introduceMacromedia Flash software to teachers of SMK Negeri 1 Takalar and to train teachers of SMK Negeri 1 Takalar tocreate learning media. The output of this study is the learningmedia used in the learning process and the improvement of thequality of learning by clarifying the presentation of messagesso that they are not verbalistic, eliminating passivity on thesubject of learning, and raising motivation in the subject oflearning. The results of this research are learning mediacreated by teachers of SMK 1 Takalar by looking at their highenthusiasm and motivation to apply the learning media. Inaddition, adequate school facilities and infrastructure and someyoung teachers who already have initial media skillspresentation media, especially Microsoft PowerPoint.